2009
DOI: 10.1073/pnas.0908074106
|View full text |Cite
|
Sign up to set email alerts
|

Early onset of autoimmune disease by the retroviral integrase inhibitor raltegravir

Abstract: Raltegravir is a recently, Food and Drug Administration-approved, small-molecule drug that inhibits retroviral integrase, thereby preventing HIV DNA from inserting itself into the human genome. We report here that the activity profile of raltegravir on the replication of murine leukemia virus is similar to that for HIV, and that the drug specifically affects autoimmune disease in mice, in which endogenous retroelements are suspected to play a role. While NZW and BALB/c mice, which do not succumb to autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 53 publications
1
28
1
Order By: Relevance
“…We found that AZT inhibited XMRV replication, as recently reported by Sakuma et al and Hong et al (20,49) and consistent with previously reported inhibition of MLV replication (22,44,56). We also found that TDF inhibits XMRV replication, albeit with less potency than HIV-1, and that raltegravir, recently reported to inhibit MLV integration (1), is a potent inhibitor of XMRV. These antiviral agents may be useful for analysis of the kinetics of XMRV replication; such studies have provided great insights into the mechanisms of HIV-1 replication and pathogenesis (4,16,66).…”
Section: Discussionmentioning
confidence: 74%
“…We found that AZT inhibited XMRV replication, as recently reported by Sakuma et al and Hong et al (20,49) and consistent with previously reported inhibition of MLV replication (22,44,56). We also found that TDF inhibits XMRV replication, albeit with less potency than HIV-1, and that raltegravir, recently reported to inhibit MLV integration (1), is a potent inhibitor of XMRV. These antiviral agents may be useful for analysis of the kinetics of XMRV replication; such studies have provided great insights into the mechanisms of HIV-1 replication and pathogenesis (4,16,66).…”
Section: Discussionmentioning
confidence: 74%
“…Protease inhibitors harbor an intermediate phenotype which is highly active against HIV-2/SIV (18) but ineffective against the Gammaretrovirus xenotropic murine leukemia virus-related virus (42). RAL and EVG were previously shown to be effective against HIV-2/SIV (21,38,40), gammaretroviruses (1,34,40,42,43), and the Spumavirus prototype foamy virus (PFV) (48), suggesting that they, like NRTIs, might harbor pantropic antiretroviral activities. To comprehensively address this question, we determined RAL and EVG concentrations required to inhibit infection by vectors derived from five different lentiviruses, the Betaretrovirus Mason-Pfizer monkey virus (MPMV), the Alpharetrovirus Rous sarcoma virus (RSV), and the Gammaretrovirus Moloney murine leukemia virus (MLV).…”
mentioning
confidence: 99%
“…However, subtle findings of nephrotoxicity were observed in the Raltegravir Switch clinical trial and in a retroviral mouse model. 4 The studies presented here do not support a direct nephrotoxic effect of integrase inhibitors in mice in the time frame examined. Serum creatinine levels of mice were reliably elevated after two weeks of RAL and DTG administration.…”
Section: Discussionmentioning
confidence: 49%
“…The concentration of RAL in water, dose administered, and route of administration follow a previously published RAL mouse model. 4 The concentration and dose for DTG were scaled to maintain a fourfold exposure as compared to the human daily dose. The two-week time point was selected as serum creatinine was reliably elevated at that time and modeled after a human study wherein two weeks of oral administration led to changes in creatinine secretion without affecting GFR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation